The Influence of Teacher Supervision, Work Culture, and Organizational Commitment on Teacher Performance at XYZ High School, Bintaro - Riyanti Riyanti; Innocentius Bernarto (Green Publisher Indonesia, 2024)
The quality of education is strongly influenced by the quality of teachers as educators. One of the desired qualities is performance, which shows the ability of teachers to achieve optimal results in the organization. The purpose of this study is to examine the effect of supervision on organizational commitment, work culture on organizational commitment, supervision on teacher performance, work culture on teacher performance, and organizational commitment on teacher performance at XYZ Bintaro High School. This study uses a quantitative approach with the PLS-SEM method to analyze the effect of the path coefficient on the variables studied. The research respondents consisted of 41 teachers at XYZ Bintaro High School who filled out a survey via Google Forms with a census approach. The data collected were then analyzed using the SEM (Structural Equation Modeling) model through the PLS 4.0 application. The results of this study indicate that supervision has a positive effect on organizational commitment, work culture has a positive effect on organizational commitment, supervision has a positive effect on teacher performance, work culture has an effect on teacher performance, and organizational commitment has a negative effect on teacher performance.